High Prevalence of Poor Sleep Quality in Chronic Foot and Ankle Conditions. Issue 4 (16th October 2019) - Kunze, Kyle N.; Wu, Kevin; Wakefield, Connor; Bohl, Daniel D.; Holmes, George B.; Lin, Johnny; Lee, Simon; Hamid, Kamran S.
Category: Ankle, Hindfoot, Midfoot/Forefoot Introduction/Purpose: Sleep disturbance is a known risk factor for poor healing and is associated with medical co-morbidities. Poor sleep quality is also a common complaint of pre-operative patients; yet, there remains a paucity of investigations in this realm. The purpose of this study is to quantify the prevalence of sleep disturbance in patients undergoing surgical management of chronic foot and ankle conditions. Methods: Patients scheduled for first-time surgical management of a chronic foot and ankle condition were identified between May and November of 2018 at a tertiary care medical center. Patients with a known sleep disorder or refusal to participate were excluded. Of 139 patients initially identified, 84 (60.4%) were included and administered the Pittsburgh Sleep Quality Index (PSQI) pre-operatively. The PSQI ranges from 0-21, with a score ±5 indicative of poor sleep quality. Patients were also asked to rate their perception of how their foot or ankle pain influenced their sleep quality on a scale of 0-10 (foot ankle pain perception score, FAPPS). A multivariate linear regression model was used to determine predictors of sleep disturbance. Results: The mean (+/- standard deviation) age of the 84 included patients was 48.2+/-13.8 years; body mass index (BMI) was 28.9+/-5.0 kg/m2; 52.4% of patients identified as male; and conditions and treatments were varied (Table 1). The mean PSQI score was 7.6+/-4.3 (range, 2-21) and mean FAPPS was 3.2+/-2.7. A total of 64 (76.2%) patients had a PSQI score greater than/equal to 5, indicating presence of sleep disturbance. A total of 68 (81.0%) patients had a FAPPS greater than/equal to 1, indicating that a patient perceived that their foot or ankle pain contributed to sleep disturbance. Age, sex, BMI, and condition/treatment category were not correlated with PSQI score (p>0.05 for each); however, greater FAPPS was an independent predictor of a greater PSQI score (p<0.001). Conclusion: Patients presenting for management of chronic foot and ankle conditions have a high prevalence of sleep disturbance pre-operatively. The majority of these patients perceive their foot and ankle conditions to significantly contribute to their sleep disturbance. Further testing assessing post-operative changes to sleep quality is warranted.